In silico modelling and structural dynamics of PRR CORE ectodomain and its interaction with PAMP csp22 - Jawad, Tanvir (BRAC University, 2019)
This thesis report is submitted in partial fulfilment of the requirement for the degree of Master of Science in Biotechnology, 2018.